A murine model of gestational diabetes reveals MASLD risk and alterations in markers of hepatic mitochondrial metabolism - Shryack, Grace E.; Krause, Alexa A.; Hernandez Ruano, Simone; Schulz, Laura C.; Pennington, Kathleen A.; Rector, R. Scott (Frontiers in Endocrinology, 2025)
IntroductionGestational Diabetes Mellitus (GDM) impacts roughly 1 in 7 pregnancies and results in metabolic dysfunction-associated steatotic liver disease (MASLD) in 30% of these women. Nonetheless, there exists a dearth of investigation into the relationship between GDM and MASLD. Here, we sought to investigate the potential role of hepatic mitochondrial function in GDM and MASLD.MethodsOne week prior to conception and throughout pregnancy, mice were fed either a low-fat control diet (CD) or a high-fat, high-sucrose (HFHS) diet to induce an established model of GDM. Maternal livers were collected at day 0, 6.5, 13.5 and 17.5 of pregnancy. Hepatic markers (via mRNA and western blot analyses) of mitochondrial biogenesis, autophagy, mitophagy, activity, and function were assessed, as well as markers of inflammation and antioxidant status were evaluated.ResultsProgressing gestation in both CD and GDM dams significantly decreased protein and mRNA markers of hepatic mitochondrial biogenesis (Pgc1-α, Tfam), autophagy (Atg5, Sqstm1), mitophagy (Pink1, Bnip3) and lipid handling (Ampk, pAMPK/AMPK, FAS, ACC, pACC, Mttp) with a main effect for time (P<0.05). HFHS-induced model of GDM lead to significant elevations in liver triglycerides and NAFLD Activity Score (NAS) (P<0.0001, P<0.0001) independent of body weight gain during gestation. MASLD development in the GDM mice occurred in conjunction with significant reductions in hepatic mitochondrial activity at day 6.5 (citrate synthase, p<0.01) and day 17.5 (β-HAD, citrate synthase, P<0.001) compared to CD mice. However, GDM lead to elevated protein and/or mRNA markers of mitochondrial biogenesis (Tfam), mitophagy (BNIP3, Bnip3, Sqstm1, Pink1), lipid handling (Mttp), inflammation (Il-1β, Tnf-α, Tgf-β) and antioxidant defense (Gxp1, Nfe2l2, Sod2) (P<0.05).DiscussionPregnancy, independent of diet, decreased markers of liver mitochondrial biogenesis, autophagy, and mitophagy in dams. The GDM mouse model exhibited elevated hepatic TG and NAS, as well as decreased liver mitochondrial activity. These findings demonstrate that pregnancy and GDM significantly impact maternal liver mitochondrial metabolism and unveil new insight on the potential relationship between MASLD and GDM.